Polymorphisms in the tumour necrosis factor gene are not associated with severity of inflammatory polyarthritis. Issue 3 (12th February 2004) - Barton, A; Platt, H; Salway, F; Symmons, D; Barrett, E; Bukhari, M; Lunt, M; Zeggini, E; Eyre, S; Hinks, A; Tellam, D; Brintnell, B; et al.
Abstract : Background: Tumour necrosis factor alpha (TNFα) is a powerful inflammatory mediator in rheumatoid and other types of inflammatory arthritis. Polymorphisms within the TNFα gene have previously been investigated to determine their role in the aetiopathogenesis of rheumatoid arthritis (RA), but it is unclear whether reported associations are with susceptibility to, or severity of, disease. Objective: To examine the association between both individual TNFα single nucleotide polymorphisms (SNPs) and haplotypes with the development and severity of erosions by 5 years in patients with inflammatory polyarthritis (IP). Methods: 438 patients from the Norfolk Arthritis Register observational inception cohort of patients with IP were x rayed 5 years after disease onset. They were genotyped for nine SNPs mapping to the TNFα gene, using a SNaPshot primer extension assay. Haplotypes were constructed in patients with IP, who were compared for the presence and extent of erosions at 5 years. Results: No association between individual TNFα SNPs or haplotypes in the patients who developed erosions at 5 years compared with those who remained non-erosive was found. Restricting analysis to patients who satisfied ACR criteria for RA by 5 years did not affect the conclusions. Conclusion: The TNFα gene does not seem to be associated with severity as assessed by erosive outcome at 5 years in patients with IP.